Hubungan Perilaku Hidup Bersih dan Sehat (PHBS) dengan Kejadian Penyakit Diare di Lingkungan Masyarakat - Rosdiana, Rosdiana; Pannyiwi, Rahmat (Barongko: Jurnal Ilmu Kesehatan, 2025)
Diarrheal disease remains a public health problem with a high prevalence in Indonesia, particularly in environments with poor hygiene and sanitation practices. Clean and Healthy Living Behavior (PHBS) plays a crucial role in preventing diarrhea through handwashing, hygienic food preparation, and good environmental sanitation. This study aims to analyze the relationship between PHBS behavior and the incidence of diarrhea in the community. The study used a cross-sectional study design, with a sample of 100 households in District X selected using cluster random sampling. Data were collected through PHBS questionnaires, home sanitation observations, and medical records or interviews regarding diarrheal episodes in the past month. Data analysis used the Chi-square test to determine the relationship between variables. The results showed that families with good PHBS behaviors had a lower incidence of diarrhea than families with poor PHBS behaviors (p = 0.002; OR = 0.35). Conclusion: There is a significant relationship between PHBS behaviors and the incidence of diarrhea in the community. Education and health promotion related to PHBS are crucial for reducing the prevalence of diarrhea.